Analysis Of Student Learning Outcomes At Smk N 1 Sintuk Toboh Gadang - Dewi, Mega Silvia; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
The background of this research is that not all of the existing facilities are in accordance with the standards set by Permendiknas No. 40 of 2008, such as there is still a lack of toilets in the school which there is only one and is far from the student study room, practical equipment is complete but not sufficient for all students to use, library staff do not inform the books in the library, lack of curiosity know from the students themselves about the existing facilities, this is what makes the value of student learning outcomes low. The purpose of this study was 1) to describe school facilities, (2) to describe student learning outcomes in the subject of Continental Food Serving at SMK N 1 Sintuk Toboh Gadang, (3) to analyze the relationship between school facilities and student learning outcomes at SMK N 1 Sintuk Toboh Gadang. The method used in this research is the method of correlation or relationship. The data analysis technique in this study uses correlation analysis. From the results of research that has been carried out using correlation analysis, it is known that the correlation coefficient between school facilities (X) and student learning outcomes (Y) is 0.205 if interpreted into an r value, then the interpreted correlation coefficient is low. The results of his research are that there is a significant relationship between school facilities and student learning outcomes.